“The Success of Gentleness”: Homosocial Desire and the Homosexual Personality in the Novels of William Godwin - Markley, A. (Romanticism on the Net, 2004)
AbstractThis article explores William Godwin’s work in his novels to expose ways in which traditional conceptions of masculinity foster aggression and rivalry between men. For Godwin, the destructiveness of such interactions profoundly threatened the potential he saw for the perfectibility of human nature and social relationships. From his early novel Imogen to the deeply psychological Caleb Williams, Fleetwood, and Mandeville, Godwin frequently illustrates the injurious potential of homosocial and homoerotic desire. In many of these instances, such desire is depicted through the use of subtle allusions to classical conceptions of friendship. In the case of Cloudesley, Godwin carries this project further, developing a persona in the hero Julian, whose gentle, feminized personality works to soften the more traditionally masculine and destructive men around him. As a new conception of the male personality, Julian exemplifies Godwin’s argument that “disinterested affection” is the only means towards a more perfect global society. In Godwin’s career as a novelist, therefore, we see an early suggestion that social progress demands a redefinition of traditional conceptions of gender.